Advancing into the details of pulmonary haemodynamics during exercise. Issue 3 (17th September 2018) - Kovacs, Gabor; Olschewski, Horst
Pulmonary haemodynamics during exercise may help us to understand why patients are severely limited despite relatively moderate pathological findings at rest. Recently, a European Respiratory Society task force presented the expert consensus on clinical experience and published studies over the past 50 years in this field [1], and suggested a definition of "exercise pulmonary hypertension" (exercise PH). In contrast to previous guidelines [2], this expert statement does not consider an isolated increase of mean pulmonary arterial pressure (MPAP) over a certain threshold during exercise as pathological. Instead, "exercise PH" is characterised by an excessive increase of MPAP in relation to the increase in pulmonary blood flow during exercise. Recent clinical studies allow better understanding of changes in pulmonary haemodynamics during exercise in different disease entities http://ow.ly/129o30lwHP2